Kebijakan Formulasi Penyidikan Tindak Pidana Terorisme - Ahmad Yunus (JURNAL RECHTENS, 2018)
Terrorism is a crime against humanity and civilization and is one serious threat to the sovereignty of every country. As a manifestation of the handling and handling of terrorist acts of terrorism the Indonesian government established national legislation. Referring to international conventions and legislation relating to terrorism, the government issued Government Regulation in Lieu of Law No. 1 of 2002, which was then approved by the House of Representatives into Law No. 15 of 2003 on Combating Terrorism Crimes. Along with the enactment of the Act on Criminal Acts of Terrorism, it appears that some of the weaknesses of the Act is one of them that is related to the process of investigation in Article 26 Paragraph 2 of the Law on Combating Terrorism Criminal which is considered too long process to the exclusion that the criminal act of terrorism is Extra Ordinary Crime (extraordinary crime). Based on the above description of the issues discussed there are 2 (two), namely: First, Is the formulation of the investigation policy in Law Number 15 Year 2003 on the Eradication of Criminal Acts of Terrorism can prevent the occurrence of criminal acts of terrorism. Second, how is the formulation policy of investigation in the Anti-Terrorism Penal Code in the future.